1
$\begingroup$

Let's consider the DE $x'=Ax$ where $$A=\begin{pmatrix}0&0&0\\1&0&-1\\0&0&-1\end{pmatrix}$$

Now, in one of my textbooks it says that for each eigenvalue $\lambda$ with algebraic multiplicity $k$ we get $k$ elements of the fundamental system via $$\begin{array} a e^{\lambda t}v_1, & e^{\lambda t}(v_2 +tv_1),&\dots &\end{array} e^{\lambda t}(v_k+\dots+t^{k-1}v_1)$$where the $v_1,\dots,v_n$ are the generalized eigenvectors corresponding to $\lambda$.

If I use this statement I first get the generalized eigenvectors via $\chi_A(\lambda)=-\lambda^2(1+\lambda)$ to be

  • $u_1=(0,1,1)$ for $\lambda_1=-1$.
  • For $\lambda_2=0$ I chose $v_1=(1,0,0)\in\ker(A^2)$ and got $v_2=Av_1=(0,1,0)^T$.

This should yield the fundamental system $$\left\{(0,1,1)e^{-t},(1,0,0),(t,1,0)\right\}$$which doesn't produce solutions if I'm not mistaken. Where is the error?

$\endgroup$
0
$\begingroup$

A Jordan block with eigenvalue $\lambda$ and multiplicity $n$ for $A$ corresponds to a cyclic subspace generated by a vector $x\ne 0$ with basis $$ \{ x, (A-\lambda I)x, (A-\lambda I)^2x,\cdots,(A-\lambda I)^{n-1}x \}. $$ And $(A-\lambda I)^nx=0$, but $(A-\lambda I)^{n-1}\ne 0$. On this cyclic subspace, $e^{tA}$ is represented by $$ e^{tA}x= e^{\lambda t}e^{t(A-\lambda I)}x \\ = e^{\lambda t}\left(x+t(A-\lambda I)x+\frac{t^2}{2!}(A-\lambda I)^2x+\cdots+\frac{t^{n-1}}{(n-1)!}(A-\lambda I)^{n-1}x\right) $$ You have cyclic subspaces for $\lambda=0,1$. The one for $\lambda=-1$ is one-dimensional. The one for $\lambda=0$ is two-dimensional. $\lambda=-1$ gives solution $$ e^{-t}\begin{pmatrix}0 \\ 1 \\ 1\end{pmatrix}. $$ $\lambda=0$ gives one solution that is constant in t, and another that is linear in $t$: $$ \begin{pmatrix}0 \\ 1 \\ 0\end{pmatrix}, \begin{pmatrix}1\\0\\0\end{pmatrix}+t\begin{pmatrix}0\\1\\0\end{pmatrix}. $$ You can directly check that all three of these satisfy the equation $\frac{d}{dt}x(t)=Ax(t)$, and the initial values of these solutions are vectors that span $\mathbb{C}^3$. So linear combinations of these three solutions form a basis of all solutions of $\frac{dx}{dt}=Ax(t)$. You formed incorrect combinations based on the statement that you quoted. It's not valid to multiply the first of these last two by $t$ and then subtract this from the second, because multiplication by $t$ changes the first into a non-solution.

$\endgroup$
2
$\begingroup$

The characteristic polynomial of your matrix $A$ is \begin{align} p(\lambda)&=\det(\lambda I-A)\\&=\left|\begin{array}{ccc} \lambda & 0 & 0 \\ -1 & \lambda & 1 \\ 0 & 0 & \lambda+1 \end{array}\right| \\ &= \lambda^2(\lambda+1). \end{align} Therefore $A^3=-A^2$. So, \begin{align} A^3 &= -A^2 \\ A^4 &= -A^3 = A^2 \\ A^5 &=-A^4 = A^3=-A^2 \end{align}

The solution of $x'(t)=Ax$ is $x(t)=e^{tA}x(0)$, where $e^{tA}=\sum_{n=0}^{\infty}\frac{t^n}{n!}A^n$, which can be simplified by the above matrix equations: $$ e^{tA} = I+tA + \left(\frac{t^2}{2!}-\frac{t^3}{3!}+\frac{t^4}{4!}-\cdots\right)A^2 \\ = I+tA+(e^{-t}-1+t)A^2 $$ So, the solution of $x'(t)=Ax(t)$ with initial condition $x(0)=x_0$ is $e^{tA}x_0$, which simplifies to

$$ x(t)=x_0+tAx_0+(e^{-t}-1+t)A^2x_0. $$

$\endgroup$
  • $\begingroup$ Thank you for your answer. But this doesn't answer my question. Where is my error? $\endgroup$ – Buh Aug 19 '18 at 17:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.